Certain generalized fractional calculus formulas and integral transforms involving (p,q)-Mathieu-type series - Agarwal, Ravi P.; Kilicman, Adem; Parmar, Rakesh K.; Rathie, Arjun Kumar (SpringerOpen, 2019)
In this paper, we establish sixteen interesting generalized fractional integral and derivative formulas including their composition formulas by using certain integral transforms involving generalized (p, q)-Mathieu-type series.